Critical thinking,problema solving and Reading comprehension in college entrants - Yarlequé Chocas, Luis Alberto (2020)
It was tried to establish yes, to a higher level of development of critical thinking there is also a greater capacity to solve problems and a higher level of reading comprehension in university entrants. The descriptive method was used, with a descriptive correlational design. We worked with 513 entrants to the National University of Central Peru, of 8 faculties, taken for accessibility and informed consent. The instruments were developed by the researchers. Some results and conclusions were that many enter with a low level of critical thinking; that in women this competence is more developed than in men; that many entrants have a low level of problem solving capacity and that there are no differences by sex. Finally, there are a large number of young people with low levels of reading comprehension; that women also outperform men in this and that critical thinking is associated with it. It follows that, to enter the university, it is not an essential requirement to have developed critical thinking, the ability to solve problems or reading comprehension, which accuses a serious limitation in the selection process.